Race and liberty in America : the essential reader - Bean, Jonathan J. (Independent studies in political economy., 2009)
"Since its emergence, the United States' two-party political system has been criticized for polarizing public opinion. Instead of objective deliberation of such major issues as race relations, partisanship has too often undermined the process and distorted the outcome. One group of thinkers, however, has refused to be defined by either conservative or liberal classifications - classical liberals have shaped the history of the nation by fighting for abolitionism and the allied struggles against Chinese exclusion, abuse of native Americans, Japanese internment, and Jim Crow and other racial distinctions in the law. Nonetheless, the nation's preoccupation with left-versus-right politics has overshadowed how classical liberals have been decisive in shaping the history of race and liberty in America. Race and Liberty in America explains the major themes of the anti-racist, classical liberal tradition of individual liberty and equality, demonstrating how it has inspired individuals to improve race relations in the United States. Rooted in the Judeo-Christian natural-law tradition, classical liberals have advocated freedom from governmental interference, abolition of prejudicial law, equality under a uniform rule of law guaranteed by the Constitution, and market-based entrepreneurial opportunity. The book offers numerous documents, from the Declaration of Independence to the 2006 Open Letter on Immigration and beyond, as well as government statutes, sermons, party platforms, and speeches that demonstrate how classical liberalism was at the forefront of the fight to change America's racial inequality. Each chapter investigates a specific time period in American history, ranging from the Revolution to the present, and addresses major events and concerns. The commentary assembled here covers the antislavery movement, post-Civil War reconstruction, Progressive Era, Republican era of the 1920s, the Great Depression and World War II, and the civil rights era. Citing such influential Americans as Thomas Jefferson, Louis Marshall, Frederick Douglass, and Booker T. Washington, plus those missing from other books and heretofore lost to history, Bean demonstrates the major impact of classical liberal thought on race relations and investigates how it has helped shape both law and public opinion"--Publisher's description